Techniques for short-term economic forecasting - Fagan, Gabriel; Fell, John P.C. (Statistical and Social Inquiry Society of Ireland, 1991)
This paper presents a survey of the techniques which can be employed in producing short term economic forecasts such as those published in the Bulletins of the Central Bank of Ireland and by other organisations. The focus of the paper is on technique rather than on the past historical performance of forecasting agencies which has been examined elsewhere (Durkan and Kelleher, 1973; Skehan 1990). It should be noted that the paper does not cover all techniques. In particular, more recent developments such as non-linear methods and the use of neural networks, for example, are not considered, since these methods are in their infancy as far as economics is concerned and are, as yet, not widely used by practitioners. A flavour of these methods can be obtained from Frain (1990).
Read before the Society, 21 February 1991
Keywords: Economic forecasting; Forecasting techniques; 314.15